Sri Lanka - Valuation of Environmental Services in Sri Lanka : A Case Study of Soil and Watershed Benefits in the Southern Province - World Bank (Washington, DC, 2013)
This 2010 report, Valuation of Environmental Services in Sri Lanka : A Case Study of Soil and Watershed Benefits in the Southern Province, uses valuation tools to evaluate environmental services to allow policymakers to efficiently address sustainable economic development and environment protection within the country s economic policy. The Government of Sri Lanka has committed to a 10-year development framework of increased growth and policymakers in the Southern Province have embarked on an ambitious program of improved roads and other large infrastructure projects. Watershed management is perhaps the most significant issue since they supply such a wide variety of environmental services to the population and environment. Due to the numerous beneficial flows it is difficult to visualize any development that would not affect any of these values to some degree.